2017
DOI: 10.5812/ijpbs.3559
|View full text |Cite
|
Sign up to set email alerts
|

Personality Patterns and Forgiveness Among University Students in Ardabil, Iran

Abstract: Background: Forgiveness is associated with many psychological and personality factors such as severe and clinical personality patterns. Objectives: The aim of this study was to determine the role of severe and clinical personality patterns in prediction of forgiveness in a sample of university students. Methods: A cross-sectional study was conducted on 375 students (175 female, 200 male) from university of Mohaghegh Ardabili in 2012-2013. The subjects were asked to fill out Millon clinical multiaxial inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Substance abuse can have a detrimental impact on various aspects of the educational setting, including the well-being and academic performance of students, campus safety, and the overall learning environment. Rezahosseini et al [17] from Rafsanjan, Iran, found a prevalence of drug abuse among university students. Benzodiazepines, cigarettes, tobacco, alcoholic drinks, and opiates were among the commonly abused substances.…”
Section: H4: Student Well-being Has a Negative Impact On The Intentio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Substance abuse can have a detrimental impact on various aspects of the educational setting, including the well-being and academic performance of students, campus safety, and the overall learning environment. Rezahosseini et al [17] from Rafsanjan, Iran, found a prevalence of drug abuse among university students. Benzodiazepines, cigarettes, tobacco, alcoholic drinks, and opiates were among the commonly abused substances.…”
Section: H4: Student Well-being Has a Negative Impact On The Intentio...mentioning
confidence: 99%
“…There are studies that indirectly implied that drug and substance abuse (i.e. [16,17]) and delinquent behaviors (i.e. [18,19]) endanger students' well-being and potentially compromise the educational environment's security.…”
mentioning
confidence: 99%
“…The most common age ambit of narcotic abusers globally is (18 -25) years. Some students are at these ages, and narcotic abuse has been shown in them; among illegal drugs, consuming (3.8%) is the most common abused narcotic in the world 27,28 .…”
Section: Introductionmentioning
confidence: 99%